DEVELOPMENT OF THE STATE IN THE TREATISE “THE STATE OF THE WRESTLER MUHAMMAD” (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2025)
This article is aimed at highlighting the blessed states, discoveries and miracles of Muhammad Kushtigir, that is, Pahlavan Muhammad, who was glorified as the sun of the nation and religion, in the treatise “The State of the wrestler Muhammad” by Hazrat Alisher Navoi, which describes the images and biography of that person. Pahlavan Muhammad’s ability in science and technology, his grace and perfection, his pleasant voice in music and his mastery of artistic methods, and the beauty of his morals are shown as the reasons for his respect and admiration among the people. Alisher Navoi describes his trainer, friend and colleague Pahlavon Muhammad as a physically and spiritually perfect person.